Multimedia Information Retrieval - Quevedo, Eduardo (IntechOpen, 2021)
Due to increasing globalization and the explosion of media available on the Internet, computer techniques to organize, classify, and find desired media are becoming more and more relevant. One such technique to extract semantic information from multimedia data sources is Multimedia Information Retrieval (MMIR or MIR). MIR is a broad area covering both structural issues and intelligent content analysis and retrieval. These aspects must be integrated into a seamless whole, which involves expertise from a wide variety of fields. This book presents recent applications of MIR for content-based image retrieval, bioinformation analysis and processing, forensic multimedia retrieval techniques, and audio and music classification.